PENGAJARAN BAHASA JAWA DI SD DAN SMP: PEMIKIRAN KE ARAH SINERGINYA ANTARA KEBIJAKAN PEMERINTAH DAN PEMBINAAN BAHASA DAERAH DI LAPANGAN - M, Udjang Pr (Pendidikan Dasar, 2009)
Abstract: Javanese represent the vernacular which old enough wide and its usage region. Till in this time, its existence still be awaked better. That matter is proven with usage in society which remain to be awaked, taught at school, and supported with a few college which remain to construct the majors of Ianguage and Java Art.Even if that way, in execution there is problem. Besides government policy which less side the, allocation of time ang less, also slimmest professional teacher energy. Various effort overcome the problem conducted by various party with the curriculum repair, levying and book development teach, and also energy construction learn, but its result not yet seethed with excitement, and surely with its position as local payload. Matter which can be conducted by besides constructing teacher, develop;building the rising generation awareness, also intensify the cooperation with local government as local policy maker, so that profit the instruction and Javanese construction